MINERAL CHEMISTRY AND THE ORIGIN OF ENSTATITE IN UNEQUILIBRATED ENSTATITE CHONDRITES - Weibiao H.; Crozaz G. (My University, 1998)
A comprehensive study of the petrography, cathodoluminescence (CL), rare earth element (REE) abundances, and magnesium and silicon isotopic compositions of enstatite, the major mineral in unequilibrated enstatite chondrites (UECs), is reported. For comparison, observations were also made in equilibrated enstatite chondrites (EECs) and aubrites. In UECs, there are no REE patterns or abundances that uniquely characterize the CL color and intensity, grain size, or occurrence of enstatite. Red enstatite is dominant in UECs and blue enstatite in EECs. Three REE patterns represent the diversity observed in UEC enstatite; many grains are depleted in one or more of the three most volatile REEs under reducing conditions (i.e., Yb, Eu, and Sm). All REE patterns are compatible with the fractional crystallization (during chondrule formation) of melts whose precursors either had flat REE patterns or were depleted in the most volatile REEs. No evidence was found to suggest that enstatite grains require nebular condensation or multiple reservoirs, as suggested by others. Magnesium and silicon isotopic ratios are normal, therefore excluding the role of evaporation in separating the REEs. This fractionation was most likely accomplished during condensation of the chondrule precursors. Our data, combined with synthetic experiments, support the idea that coexisting red and blue CL enstatites formed by crystallization from a single melt. Most of the red enstatite was converted to blue by diffusion and recrystallization to form the more equilibrated E chondrites. It is not clear why enstatite is depleted in the most volatile REEs while oldhamite, a highly refractory mineral which is the major carrier of REE in E chondrites, commonly has enrichments of these elements.